Impact of COVID-19 on quality of life in survivors with pulmonary sequelae - Rodríguez-Galán, Irene; Albaladejo-Blázquez, Natalia; Ruiz-Robledillo, Nicolás; Pascual-Lledó, José Francisco; Ferrer-Cascales, Rosario; Gil-Carbonell, Joan (Springer Nature, 2024)
SARS-CoV-2 respiratory infection is still under study today, mainly because of its long-term effects. This study aims to analyse health status and health-related quality of life (HRQoL) in survivors of coronavirus pneumonia (COVID-19) who have developed pulmonary sequelae. Prospective observational study of patients diagnosed with COVID-19 pneumonia between February and May 2020. Reviews were conducted at 3 and 12 months after hospital discharge. HRQoL was assessed by administration of the SF-36 questionnaire and data related to medical records and physical examination were also collected. In addition, chest X-ray, computed tomography and pulmonary function test were included as additional tests. 305 patients were admitted for COVID-19 pneumonia of which 130 (42.6%) completed follow-up. The mean age of the enrolled group was 55.9 ± 15.9 years. The most prevalent persistent symptoms were dyspnea (37.3%) and asthenia (36.9%). Pulmonary sequelae were detected in 20.8% of participants. The most frequent alteration was ground ground glass opacities (GGO) (88.9%), with mild extension. Fibrotic changes were found in only 2% of cases. When comparing the two groups, at 3 and 12 months of evolution, lower scores in the vitality (VT) and mental health (MH) domains were found only in the group without sequelae. Days of hospitalisation and Charlson index acted as influential factors on HRQoL. Minimal or mild pulmonary sequelae of SARS-CoV-2 do not cause further deterioration of HRQoL. Repeated medical care and pulmonary rehabilitation are effective tools to improve HRQoL.
Keywords: SARS-CoV-2 pneumonia; COVID-19; Health-related quality of life; Sequelae; Life quality; Pulmonary fibrosis